2017
DOI: 10.1038/npp.2017.41
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Modafinil Analog, JJC8-016, as a Potential Cocaine Abuse Pharmacotherapeutic

Abstract: (±)Modafinil ((±)MOD) and its R-enantiomer (R-modafinil; R-MOD) have been investigated for their potential as treatments for psychostimulant addiction. We recently reported a series of (±)MOD analogs, of which JJC8-016 (N-(2-((bis(4-fluorophenyl)methyl)thio)ethyl)-3-phenylpropan-1-amine) was selected for further development. JJC8-016 and R-MOD were evaluated for binding across ~70 receptors, transporters, and enzymes. Although at a concentration of 10 μM, there were many hits for JJC8-016, binding affinities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 85 publications
2
37
0
Order By: Relevance
“…Like cocaine, (±)-modafinil is a stimulant (Young et al, 2011) and has been reported to have reinforcing properties in rhesus monkeys (Gold and Balster, 1996). Nevertheless, neither the racemate nor R-modafinil is self-administered in rodents and they do not exhibit abuse liability in humans, despite a mechanism of action that might predict this (Mereu et al 2013 and 2017, Volkow et al 2009; Zhang et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Like cocaine, (±)-modafinil is a stimulant (Young et al, 2011) and has been reported to have reinforcing properties in rhesus monkeys (Gold and Balster, 1996). Nevertheless, neither the racemate nor R-modafinil is self-administered in rodents and they do not exhibit abuse liability in humans, despite a mechanism of action that might predict this (Mereu et al 2013 and 2017, Volkow et al 2009; Zhang et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…In contrast however, JHW 007 decreased IPSC amplitude in a manner consistent with D2 receptor antagonism. Unlike cocaine and R-modafinil (Zhang et al, 2017), JHW 007 has affinity for the D2L receptor (47.1 nM, Katz et al, 2004) and is a weak D2 receptor antagonist (IC 50 = 2 μM, Cao et al, 2016) in addition to exhibiting 12 nM binding affinity for DAT (Kopajtic et al, 2010). This could explain how mid-micromolar concentrations of JHW 007 reduced DA-mediated current amplitudes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations